The Efficacy of Whole-Body Vibration for Functional Improvement of Stroke Patients: A Meta-Analysis of Randomized Controlled Trials - Yue, Lin; Chen, Linglong; Zhou, Rongrong (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
The efficacy of whole-body vibration for functional improvement in stroke patients remains controversial. We conduct a systematic review and meta-analysis to explore the influence of whole-body vibration on functional improvement in stroke patients.We search PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through June 2018 for randomized controlled trials (RCTs) assessing the effect of whole-body vibration on functional improvement in stroke patients. This meta-analysis is performed using the random-effect model.Eight RCTs are included in the meta-analysis. Overall, compared with control group for stroke patients, whole-body vibration has no positive impact on 6 min walk test (6MWT) distance (standard mean difference (Std. MD)=−0.28; 95% confidence interval (CI)=−0.66 to 0.11; P=0.16), timed-up-and-go (TUG) test (Std. MD=0.15; 95% CI=−0.54 to 0.84; P=0.67), Fugl-Meyer assessment (Std. MD=0.33; 95% CI=−0.23 to 0.89; P=0.25), Berg Balance Scale (Std. MD=0.19; 95% CI=−0.43 to 0.80; P=0.55), and activities specific balance (ABC) scale (Std. MD=−0.22; 95% CI=−0.62 to 0.17; P=0.26).Whole-body vibration shows no notable influence on 6MWT distance, TUG test, Fugl-Meyer assessment, Berg Balance Scale, and ABC scale in stroke patients.
Keywords: whole-body vibration; functional improvement; stroke; randomized controlled trials; meta-analysis